2014
DOI: 10.1557/mre.2014.7
|View full text |Cite
|
Sign up to set email alerts
|

From highly graphitic to amorphous carbon dots: A critical review

Abstract: Graphitic and amorphous C-dots share common characteristics in their photoluminescence behavior. However, the graphitic dots have a lead as electrocatalyst for fuel cells, sensitizers, and electron acceptors for solar cells.The emergence of carbogenic nanoparticles (C-dots) as a new class of photoluminescent (PL) nanoemitters is directly related to their economical preparation, nontoxic nature, versatility, and tunability. C-dots are typically prepared by pyrolytic or oxidative treatment of suitable precursors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
45
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(49 citation statements)
references
References 95 publications
1
45
0
Order By: Relevance
“…Furthermore, XRD pattern was collected to characterize the crystalline nature of the CDs (see Figure c). The pattern presented several peaks centered at 20.4°, 27.3°, 31.77°, 45.3°, 56.2°, 66.2°, 75.2°, corresponding to the peaks of the acid fuchsin (JCPDS: 09‐0819) without lattice structure in the CDs, indicating that the resultant CDs have an amorphous nature …”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, XRD pattern was collected to characterize the crystalline nature of the CDs (see Figure c). The pattern presented several peaks centered at 20.4°, 27.3°, 31.77°, 45.3°, 56.2°, 66.2°, 75.2°, corresponding to the peaks of the acid fuchsin (JCPDS: 09‐0819) without lattice structure in the CDs, indicating that the resultant CDs have an amorphous nature …”
Section: Resultsmentioning
confidence: 99%
“…It has been reported that stronger photoluminescence (PL) of CQDs can be observed by replacing the oxygen‐containing surface functional groups with nitrogen‐rich groups . These functional groups can be introduced during synthesis or post synthesis with additional surface treatment . The chemical nature of these functional groups strongly dependent on the specific synthesis methods and precursors used .…”
Section: Figurementioning
confidence: 99%
“…1) due to their high stability, low cytotoxicity and their tuneable photoluminescence (PL) properties. [2][3][4] However, their preparation oen requires harsh conditions. 2,3 In addition to carbon nanoparticles, conjugated polymer nanoparticles (CPNs) are also interesting counterparts to QDs due to their low cytotoxicity and tuneable optical properties for electronic devices and biological applications.…”
Section: Introductionmentioning
confidence: 99%